2010
DOI: 10.4137/cmped.s4311
|View full text |Cite
|
Sign up to set email alerts
|

Similar Results in Children with Asthma for Steady State Pharmacokinetic Parameters of Ciclesonide Inhaled with or without Spacer

Abstract: Background:Ciclesonide is an inhaled corticosteroid administered by a metered dose inhaler (MDI) to treat bronchial asthma. After inhalation, the inactive ciclesonide is converted by esterases in the airways to active metabolite desisobutyryl-ciclesonide (des-CIC).Aim:To compare the pharmacokinetic (PK) parameters of des-CIC in children after administration of therapeutic dose of ciclesonide with and without spacer (AeroChamber Plus™).Methods:Open-label, 3 period, cross over, repeated dose, PK study in 37 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
(84 reference statements)
1
10
0
Order By: Relevance
“…. The data were derived from in vitro studies , from studies in healthy males and healthy males and females , from studies in males and females and children with asthma, and from review papers . The studies in adults comprised populations of 6 , 8 , 9 and 12 subjects; the paediatric studies 18 and 34 pre‐pubertal children.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 3 more Smart Citations
“…. The data were derived from in vitro studies , from studies in healthy males and healthy males and females , from studies in males and females and children with asthma, and from review papers . The studies in adults comprised populations of 6 , 8 , 9 and 12 subjects; the paediatric studies 18 and 34 pre‐pubertal children.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The data were derived from in vitro studies , from studies in healthy males and healthy males and females , from studies in males and females and children with asthma, and from review papers . The studies in adults comprised populations of 6 , 8 , 9 and 12 subjects; the paediatric studies 18 and 34 pre‐pubertal children. Treatments were single doses of 6.9 mg (oral administration) and 0.64 mg (intravenous administration) ciclesonide , a single dose of ciclesonide 40 μg , 6‐day treatment with 50 and 100 μg beclomethasone dipropionate , a single dose of 1280 μg ciclesonide , a single dose of 200 and 400 μg beclomethasone dipropionate , and 7‐day treatment with ciclesonide 80 and 160 μg/day .…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Drollmann et al observed that the pharmacokinetic properties of the active metabolite des-CIC were comparable after inhalation with and without an AeroChamber Plus ® (Trudell Medical International, London, Ontario, Canada) spacer,46 suggesting that CIC-HFA pMDI does not require a spacer for optimal delivery. The results from a pediatric study that enrolled children (aged 6–11 years) indicated that the use of a spacer resulted in a slight increase in the systemic exposure of des-CIC and also showed that inhaled CIC (80 μg and 160 μg) with spacer led to dose proportional systemic exposure 47. There is some evidence which suggests the use of a spacer device enhances pMDI therapy by reducing the amount of drug deposited in the oropharyngeal region, leading to fewer instances of local and systemic side effects.…”
Section: Optimizing the Use Of Inhaler Devicesmentioning
confidence: 99%